Detection of Salmonella and Escherichia coli along the Fish Value Chain in Bahir Dar City, Ethiopia - Temesgen Sendekie Ayalew; Habtamu Tassew Tarekegn; Belayneh Getachew Ayalew (Wiley, 2024)
ABSTRACT Background Fish is a possible source of foodborne infections with Salmonella and Escherichia coli. This study was conducted to identify Salmonella and E. coli along the fish value chain in Bahir Dar City, Ethiopia. Methods A cross‐sectional study was undertaken with purposive sampling. A total of 121 specimens comprising fresh fish, retailing fish, filleted and cooked fish, swabs, and water samples were collected. Both culture based and molecular methods were used for detection. Results E. coli isolated from 41 (33.88%) and Salmonella from 6 (4.96%) specimen. The highest E. coli isolation rate was from retailing fish 16 (80%), whereas the highest Salmonella isolation rate from filleted tissue 2 (20%). At restaurants, 12 (30%) samples were positive for E. coli and 3 (7.50%) for Salmonella. All 41 E. coli isolates were resistant to amoxicillin/clavulanate, whereas no resistance was shown for gentamicin and amikacin. Two thirds of Salmonella isolate and 95.12% of E. coli were detected as they develop multidrug resistance. The highest rate of resistance was recorded for ceftazidime against all (n = 6) isolates of Salmonella species. From a total of 10 E. coli isolates tested by PCR, 4 were positive for hemolysin A1 and/or eae virulence genes. Conclusions The study detects the potential biological hazards along the value chain. Hygiene of fish handlers and their working environment and proper fish cooking are highly valuable. One health campaign should be carried out on drug resistance, contamination of the lake, and fish safety.